Uji Aktivitas Antibakteri Rebusan dan Infusa Daun Jeruju (Achantus illicifolious) terhadap Bakteri Methicilin Resistant Staphylococcus aureus (MRSA) - Maria Dewi, Ni Putu; Cahyaningsih, Erna; Arman Anita Dewi, Ni Luh Kade; Surya Rahadi, I Wayan; Sandhi Kusuma Yuda, Putu Era; Santoso, Puguh (Usadha, 2024)
Infectious diseases are still a health problem throughout the world, including in Indonesia. One cause of infection that needs to be watched out for is resistance to Methicillin-Resistant Staphylococcus aureus (MRSA) bacteria. Continuous use of antibiotics can cause problems with microbial resistance. Indonesia has various plant species that can actually provide benefits but have not been specifically cultivated. Jeruju leaves (Achanthus ilicifolius) from mangrove plants contain bioactive compounds that have the potential to be antibacterial. The aim of this research is to determine the antibacterial activity of Jeruju leaf decoction and infusion against MRSA bacteria. Antibacterial activity testing uses MRSA bacteria. The results of the phytochemical screening of Jeruju leaf infusion contained secondary metabolite compounds in the form of flavonoids, tannins, saponins and quinones. Meanwhile, the results of the phytochemical screening of Jeruju leaf decoction contained secondary metabolites in the form of tannins, saponins and quinones. Based on the results of research conducted on infusions and decoctions of Jeruju leaves at concentrations of 30%, 60% and 90%, they did not have inhibitory power on the antibacterial activity of MRSA, as seen from the inhibition zone. Zero inhibition zone for MRSA bacteria. It can be concluded that the infusion and decoction of Jeruju (Achantus illicifolious) leaves do not have antibacterial activity against MRSA.